İrşâdü’s-sârî li-şerhi Sahîhi’l-Buhârî - 880-01 Kastallânî, Ahmed b. Muhammed, 1448-1517. (Bulak Bulak)
10 cilt (1. c. 519 sayfa ; 2. c. 480 sayfa ; 3. c. 448 sayfa ; 4. c. 456 sayfa ; 5. c. 444 sayfa ; 6. c. 476 sayfa ; 7. c. 488 sayfa ; 8. c. 489 sayfa ; 9. c. 463 sayfa ; 10. c. 492 sayfa)